Evolution of de Winter syndrome to Wellens syndrome: a case report and literature review - Wang, Fei; Zhang, Xuesong; Pang, Huihui; Wang, Yuehai (Frontiers in Cardiovascular Medicine, 2025)
Both de Winter syndrome and Wellens syndrome mainly indicate severe stenosis in the proximal segment of the anterior descending coronary artery. However, as research deepens, the accuracy and specificity of diagnosing proximal left anterior descending coronary artery (LAD) culprit lesions separately by de Winter syndrome or Wellens syndrome are challenged. The patient in this case developed both syndromes in a short period of time, and imaging showed significant stenosis of the proximal LAD, indicating a culprit lesion. The successive appearance of these two special electrocardiogram changes may increase the accuracy and specificity of diagnosing LAD as a culprit lesion, and the short-term occurrence of these two special electrocardiogram changes also suggests that the culprit lesion may be incomplete occlusion. In addition, de Winter syndrome is prone to missed diagnosis, while Wellens syndrome is prone to misdiagnosis or underestimation of its risk.